Implications of remote education in Angolan higher education in the context of the Covid-19 pandemic: Analysis of the experience of the Benguela polytechnic institutes (International Seven Journal of Multidisciplinary, 2024)
The emergence of the COVID-19 pandemic has brought profound transformations in various spheres of society, forcing countries to adapt their education systems as strategies for interrupting teaching. Accordingly, this article deals with the implications of the teaching and learning model adopted and applied during the Covid-19 period for higher education, based on an analysis of the experiences of the ISPB and ISPM. The text explores the notion of remote education as a teaching system that allows the continuity of classes in the context of a pandemic crisis - at the same time as establishing the difference with distance learning. The study was conducted using bibliographical research and a quantitative approach. The data collection instrument adopted was a questionnaire, applied in two ways: online via Google form and face-to-face. The results led to the conclusion that students expressed a higher level of dissatisfaction with the application of remote education during the pandemic. What's more, the online solutions applied during this period were not significantly productive. A large proportion of them did not participate in online classes due to lack of financial resources, digital resources and lack of motivation. It can also be seen that, in general, the level of interaction and collaboration in all instances was somewhat weak. However, despite all the constraints, the study reveals that some of those who took part in the online study, i.e. remote education, were able to develop some collaborative skills, and that the online classes contributed to improving meaningful learning.